2016
DOI: 10.1039/c6an00744a
|View full text |Cite
|
Sign up to set email alerts
|

A one-step colorimetric acid–base titration sensor using a complementary color changing coordination system

Abstract: We report the development of a colorimetric sensor that allows for the quantitative measurement of the acid content via acid-base titration in a single-step. In order to create the sensor, we used a cobalt coordination system (Co-complex sensor) that changes from greenish blue colored Co(H2O)4(OH)2 to pink colored Co(H2O)6(2+) after neutralization. Greenish blue and pink are two complementary colors with a strong contrast. As a certain amount of acid is introduced to the Co-complex sensor, a portion of greenis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Therefore, the effect on basic environmental conditions such as pH, relative humidity, and temperature is insignificant. However, it should be noted that colorimetric sensor performance under normal conditions can be affected by the aforementioned environmental factors 89,90 . Thus, it is important to consider these environmental and mechanical factors when designing and testing colorimetric sensors 91–93 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the effect on basic environmental conditions such as pH, relative humidity, and temperature is insignificant. However, it should be noted that colorimetric sensor performance under normal conditions can be affected by the aforementioned environmental factors 89,90 . Thus, it is important to consider these environmental and mechanical factors when designing and testing colorimetric sensors 91–93 .…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that colorimetric sensor performance under normal conditions can be affected by the aforementioned environmental factors. 89,90 Thus, it is important to consider these environmental and mechanical factors when designing and testing colorimetric sensors. [91][92][93] Considering these perspectives, several research results on detecting SO 2 have been compared with our work (Table 1).…”
Section: Consideration Of the Operation Standards Of Gis Bymentioning
confidence: 99%
“…AuNPs are advantageous as colorimetric transducers for water pollutant detection as they exhibit relatively low cost, low toxicity, high stability, facile processability, and unique optical properties. In general, colorimetric sensors do not require bulky and expensive analysis instruments such as Fourier transform infrared spectroscopy or Raman spectroscopy. From that point of view, metal nanomaterials, including AuNPs, have been commonly used as sensing probes in the food, pharmaceutical, environmental, and biological fields due to their cost effectiveness . For example, research has shown that arsenic­(V) can be detected inexpensively ($0.03 per test) using a colorimetric dipstick method .…”
Section: Advantages Of Aunps As Colorimetric Transducers For Water Po...mentioning
confidence: 99%
“…In recent years, analytical chemists have made considerable efforts toward developing new methods for determining alkalinity. Van der Schoot used Coulomb titration to measure the charge at a specified pH and determine the acid–base concentration. Wiorek et al developed an alkalinity sensor based on the linear relation between the charge released by a PANI membrane and the bicarbonate concentration in the sample. , Cho et al reported a cobalt complex sensor that quantifies the acidity in the sample through color change . Nogueira et al used a natural pH indicator derived from Rosa roxburghii peel and a smartphone app called Photometrix to conduct quantitative analysis of the color of the wax paper microarea and determine the concentration of acid and base .…”
Section: Introductionmentioning
confidence: 99%